Beyond SARS-CoV-2: could MERS-CoV spark the next coronavirus pandemic? A one health perspective - Goshen David Miteu (Discover Public Health)
Abstract The COVID-19 pandemic demonstrated the lethal potential of emerging zoonotic viruses, particularly coronaviruses. While global attention has largely centered on SARS-CoV-2, Middle East Respiratory Syndrome Coronavirus (MERS-CoV) remains an overlooked yet credible pandemic threat. The objective of this commentary is to spotlight the virological, epidemiological, and evolutionary features of MERS-CoV and its potential to trigger the next coronavirus pandemic. MERS-CoV, characterized by its high case fatality rate (~ 34%) and persistent circulation in dromedary camels, continues to cause sporadic outbreaks with limited human-to-human transmission. However, the inherent mutability of RNA viruses raises concerns that adaptive mutations could enhance MERS-CoV’s transmissibility, potentially transforming it into a highly contagious human pathogen. This commentary revisits the virology, epidemiology, and zoonotic dynamics of MERS-CoV, highlighting the risks posed by viral evolution, the ongoing “slow burn” of zoonotic spillovers, and the dangers of post-pandemic complacency. We argue for renewed investment in surveillance, vaccine development, and proactive public health measures, grounded in a One Health approach. Vigilant monitoring of MERS-CoV and other emerging pathogens is essential to prevent future pandemics and to avoid being caught off guard once again.